A study on the issue of access, cost, and quality of Information Communication Technology provided to the Malaysian End-Users by The Service and Content Providers in Malaysia / Roziah Naam - Naam, Roziah (2002)
Information Communication Technologies (ICT), in its myriad forms, is having a profound and palpable impact on IT users and their environment. In its various manifestations, ICT is use as a platform to process data, gathers information, stores collected materials, accumulates knowledge, and expedites communication. In the effort to bring a more cohesive computer mediated environment to the Malaysian society, there are emerging issues that related to access, cost, and quality information. This demands a serious plan of actions to at least provides a framework for both parties to react: the providers and end-users. The main concern is to enable a better speed of data communication at an affordable price for quality information that can be leverage for the competitive advantage economically. In addition, a more customized local solutions and applications are suggest containing the issues on cost and it is also seen as an effort to widen the subscriber base in the niche market.